673 views
0 votes
For the functions f(x)=−9x^2+9 and g(x)=8x^2+9x, find (f+g)(x) and (f+g)(−1)

User Enashnash
by
5.5k points

1 Answer

4 votes

Answer:

f(x) = - 9x² + 9

g(x) = 8x² + 9x

To find (f+g)(x) add g(x) to f(x)

That's

(f+g)(x) = -9x² + 9 + 8x² + 9x

Group like terms

(f+g)(x) = - 9x² + 8x² + 9x + 9

(f+g)(x) = - x² + 9x + 9

To find (f + g)(- 1) substitute - 1 into (f+g)(x)

That's

(f + g)(- 1) = -(-1)² + 9(-1) + 9

= - 1 - 9 + 9

= - 1

Hope this helps you

User Seaders
by
5.6k points